Structuring national emergency management towards sustainability development for UAE: A conceptual approach - Alhammadi, Ali Ahmed; Wan Mahmood, Wan Hasrulnizzam (Allied Business Academies, 2022)
Natural disasters usually have an impact on both the economy, considering its available resources, as well as the society. Therefore, the national crisis and emergency authorities (NCEMA) may engage through a structured sustainability development that align with the distribution of resources and budgeting to enhance the process of preparedness during national emergencies. Though the UAE has been faced with major disasters in the past years, the process of disaster management has been complicated as the NCEMA has had difficulties in ensuring the process for disaster management, preparation, and recovery. Consequently, a lack of quality resource allocation due to management practices and framework causes an increase in wastage, as well as the lack of preparation and recovery. It also affects the community growth with the process of returning way of life to normalcy, taking more time at a higher cost. Thus, the objective of this paper intending to propose a new framework to integrate the resources management and disaster management approach for national emergency. This will encourage the NCEMA to profit by global ability and empower the coordination of logical, specialized, and human endeavors to react to crises and catastrophes. Besides that, the framework allows the UAE to ensure the quality allocation of resources, which in turn prepares it and its citizens in case any disaster takes place and enhances different policies to sustain the level of emergency preparedness. Although this study focuses on national emergency, the findings may well have a bearing on the others kind of management fields as well.